Morbidity and mortality weekly report, Vol. 8, no. 4, For release February 6, 1959 - United States Dept. of Health, Education, and Welfare Public Health Service; United States National Office of Vital Statistics
Provisional information on selected notifiable diseases in the United States and on deaths in selected cities for week ended January 24, 1959 -- Number of deaths in 114 selected cities -- Quarantine measures, immunization information for international travel Epidemiological reports: Influenza -- Salmonella -- Infectious hepatitis -- Blastomycosis Table 1. Cases of specified notifiable diseases: continental United States -- Table 2. Cases of specified notifiable diseases: United States, each division and state, Hawaii, and Puerto Rico, for weeks ended February 1, 1958 and January 31, 1959 -- Table 3. Deaths in 114 selected cities by geographic division -- Table 4. Deaths in selected cities